Offensive Strategy of Daejeon Jungkwanjang Red Sparks: A Tactical Study in the 2023–2024 V-League Season (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the attacking strategy employed by the Daejeon JungKwanJang Red Sparks professional volleyball team in the 2023/2024 South Korean V-League competition. The analysis focused on nine key indicators of attack. This study used a quantitative approach with an analytic descriptive design. The instrument used for the match analysis is Kinovea 0.9.5. The results showed that the Red Sparks team's attacking strategy relied heavily on the contributions of the two leading players. Giovanna dominated in the open attack aspect with 194 attacks and jump serve 99 times, while Megawati excelled in back attack 122 times and 3-meter attack 93 times. Meanwhile, other players such as Park Hye-min, So Young Lee, and Se-in Kim played a role in supporting the variety of attacks through float serves and attack blocks.  The findings confirm that Red Sparks' success in reaching third place in the league is not only due to the players' physical and technical abilities, but also to the implementation of innovative, flexible, and contextual attacking strategies. This research is expected to serve as a reference for coaches, players, and academics in understanding the dynamics of attacking strategies at the professional level, as well as in developing more effective tactical approaches in modern volleyball games.